Angiotensin‐Converting Enzyme Inhibitors and Alzheimer's Disease Progression in Older Adults: Results from the Réseau sur la Maladie d'Alzheimer Français Cohort. Issue 9 (3rd September 2013) - Soto, Maria E.; Abellan van Kan, Gabor; Nourhashemi, Fati; Gillette‐Guyonnet, Sophie; Cesari, Matteo; Cantet, Christelle; Rolland, Yves; Vellas, Bruno
<x xml:space="preserve">Abstract</x> Objectives To assess whether angiotensin‐converting enzyme inhibitor (ACE‐I) treatment is associated with less cognitive decline in older adults with Alzheimer's disease (AD) than in those using other hypertensive or no drugs. Design Four‐year prospective multicenter cohort study with a biannual assessment. Setting Memory clinics from 16 university hospitals in France. Participants Community‐dwelling older adults with mild to moderate AD (N = 616). Measurements Participants were stratified into four groups according to type and duration of antihypertensive drug treatment. Cognitive decline was assessed using the Mini‐Mental State Examination (MMSE). Linear mixed‐effects models were used to assess differences in decline in MMSE score between the four groups. Hypertension at each visit was included in the model. Results Sixty‐one participants had used ACE‐Is continuously, 57 had used them intermittently, 189 had used other antihypertensive drugs, and 309 never used any antihypertensive drugs. Continuous ACE‐Is users had a 4‐year decline in MMSE of 6.4 ± 1.6 points (P < .001), intermittent ACE‐Is users of 7.9 ± 1.1 points (P < .001), continuous or intermittent users of other antihypertensive drugs of 8.8 ± 0.7 points (P < .001), and never‐users of 10.2 ± 0.6 points (P < .001). MMSE decline between the four groups was significantly different (adjusted P = .02). In subgroup analysis, the 118 (19.2%) participants who had continuously or intermittently used ACE‐Is had a significant difference in 4‐year MMSE decline from the 498 (80.8%) who had never used ACE‐Is (7.5 ± 0.9 vs 9.7 ± 0.4; P = .03). Conclusion The use of ACE‐Is in older adults with AD is associated with a slower rate of cognitive decline independent of hypertension. Future research is needed to explore the role of ACE‐Is in long‐term AD progression.